Survival, development and reproduction of Phenacoccus solenopsis (Hemiptera: Pseudococcidae) on kaolin-treated cotton - V. S. Guedes; C. A. D. Silva; J. C. Zanuncio (Brazilian Journal of Biology, 2019)
Abstract The mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is a cotton pest widespread in several cotton growing regions of Brazil, particularly in the semi-arid region of southwestern Bahia. The impact of kaolin on survival, development and reproduction of P. solenopsis was evaluated in the laboratory. The experiment was developed in a completely randomized design with two treatments: immature or newly emerged adults of P. solenopsis sprayed with kaolin and fed with cotton leaf discs treated with kaolin suspension (with kaolin) (T1) and immature or newly emerged adults of P. solenopsis sprayed with distilled water and fed with cotton leaf discs treated with distilled water (without kaolin) (T2). The kaolin suspension shortens the life cycle, increases the reproductive potential and population growth of the cotton mealybug, P. solenopsis and, therefore, it should be used with caution on cotton plants in regions with a history of occurrence of this pest.